2017
DOI: 10.1111/ijal.12183
|View full text |Cite
|
Sign up to set email alerts
|

Production of ambiguous idioms in English: A reading aloud study

Abstract: In a reading‐aloud experiment, we investigated the on‐line processing of English idioms from a production perspective. The stimuli were ambiguous idioms used figuratively and literally, and matched novel control phrases. The analysis of the articulatory durations showed a processing advantage for idioms over controls. Further, we found that figurative meanings were articulated somewhat faster than their literal counterparts. The results suggest that the processing advantage for idioms over control phrases, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Despite the variety of research methods being used, these investigations confirmed the processing advantage for figurative FSs over novel phrases in sentence context and in both decomposable and non-decomposable figurative FSs. The processing advantage for figurative FL over novel language was also confirmed in recent investigations (post-2010; e.g., Hallin & Van Lancker Sidtis, 2017;Jolsvai, McCauley, & Christiansen, 2013;Rommers, Dijkstra, & Bastiaansen, 2013;Siyanova-Chanturia & Lin, 2018).…”
Section: The Processing Of Figurative Formulaic Language In L1supporting
confidence: 77%
See 4 more Smart Citations
“…Despite the variety of research methods being used, these investigations confirmed the processing advantage for figurative FSs over novel phrases in sentence context and in both decomposable and non-decomposable figurative FSs. The processing advantage for figurative FL over novel language was also confirmed in recent investigations (post-2010; e.g., Hallin & Van Lancker Sidtis, 2017;Jolsvai, McCauley, & Christiansen, 2013;Rommers, Dijkstra, & Bastiaansen, 2013;Siyanova-Chanturia & Lin, 2018).…”
Section: The Processing Of Figurative Formulaic Language In L1supporting
confidence: 77%
“…The processing advantage for L1 FSs, figurative or literal, over infrequent novel phrases has long been affirmed in the literature (e.g., Arnon & Snider, 2010;Ellis et al, 2009;Janssen & Barber, 2012;Jolsvai et al, 2013;Millar, 2011;Molinaro et al, 2008;Siyanova-Chanturia et al, 2017;Siyanova-Chanturia & Lin, 2018;Swinney & Cutler, 1979;Vespignani et al, 2009). However, the relevant evidence The answer is yes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations